2023
DOI: 10.3390/en16083396
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Methodology for Strengthening Stability in Electrical Power Systems by Considering Fast Voltage Stability Index under N − 1 Scenarios

Abstract: An electrical power system (EPS) is subject to unexpected events that might cause the outage of elements such as transformers, generators, and transmission lines. For this reason, the EPS should be able to withstand the failure of one of these elements without changing its operational characteristics; this operativity functionality is called N−1 contingency. This paper proposes a methodology for the optimal location and sizing of a parallel static Var compensator (SVC) in an EPS to reestablish the stability co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For instance, if a utility expects high energy demand during a specific time, it may activate additional generators or introduce demand response programs to lessen energy usage during peak hours. This proactive approach guarantees that the power system remains dependable and robust, despite changing energy demands and potential disturbances [12].…”
Section: Problem Formulation and Methodologymentioning
confidence: 99%
“…For instance, if a utility expects high energy demand during a specific time, it may activate additional generators or introduce demand response programs to lessen energy usage during peak hours. This proactive approach guarantees that the power system remains dependable and robust, despite changing energy demands and potential disturbances [12].…”
Section: Problem Formulation and Methodologymentioning
confidence: 99%
“…Harish et al used the fast voltage stability index (FVSI) and line stability index (L mn ) to identify the location of flexible alternating current transmission system (FACTS) devices along with PSO, artificial bee colony (ABC), and the hybrid genetic algorithm (H-GA) to find the sizing of the FACTS devices [24]. Also, a novel method for strengthening PS stability was proposed by Jaramillo et al [25]. FVSI was used to identify the node on which the SVC should be installed under an N-1 scenario.…”
Section: Introductionmentioning
confidence: 99%
“…FVSI was used to identify the node on which the SVC should be installed under an N-1 scenario. It was reported that the result obtained could reestablish the FVSI in each contingency before the outage [25]. The voltage collapse critical bus index (VCCBI) [26], L-Index, voltage collapse proximity index (VCPI), and modal analysis [27], which are part of voltage stability indices (VSI), were used to identify weak/vulnerable buses in electrical power systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among the main processes to be considered in power systems is the voltage stability of the EPS, for which optimal power flows, optimal line switching, system restoration, and the location of compensation elements, among other techniques that can be applied, are analyzed [4,5]. All of these methodologies have a direct impact on EPS losses and reactive dispatch.…”
Section: Introductionmentioning
confidence: 99%